Use of an aiming device and computed tomography for assisted debridement of subchondral cystic lesions in the limbs of horses. (31st October 2018) - Jackson, Michelle A.; Ohlerth, Stefanie; Fürst, Anton E.
Abstract: Objective: To describe the use of an aiming device (AD) and computed tomography (CT) for preoperative planning and intraoperative guided debridement of subchondral cystic lesions (SCL) in the limbs of horses and to determine the outcome 12 months after surgery. Study design: Prospective case series. Animals: Twelve horses referred because of lameness caused by 1 or 2 SCL (total of 14 SCL). Methods: All horses underwent CT‐guided debridement of the SCL. The entry point of the drill bit and direction of drilling were planned and controlled by using a series of CT images and the AD. The SCL were curetted and filled with recombinant human bone morphogenetic protein‐2. Surgical times were calculated, and the outcome was determined 12 months after surgery. Results: The use of an AD and CT allowed precise and straightforward drilling of the SCL. The entry point of the drill bit into the SCL was considered optimal in 11 SCL and satisfactory in 3 SCL, and the lesions could be precisely debrided with preservation of the adjacent subchondral bone in all cases. There were no complications. Mean (range) surgery time was 75 (45–115) minutes. The outcome 12 months postoperatively was favorable in 10 of 11 horses. One horse died due to unrelated reasons. Conclusion: The use of CT and an AD allowed precise debridement of all SCL in the limbs of 12 horses. Clinical significance: CT‐guided surgical debridement of SCL of the equine digit appears to result in a favorable outcome.